2018
DOI: 10.1016/j.buildenv.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A study on influential factors of occupant window-opening behavior in an office building in China

Abstract: Occupants often perform many types of behavior in buildings to adjust the indoor thermal environment. In these types, opening/closing the windows, often regarded as window-opening behavior, is more commonly observed because of its convenience. It not only improves indoor air quality to satisfy occupants' requirement for indoor thermal comfort but also influences building energy consumption. To learn more about potential factors having effects on occupants' window-opening behavior, a field study was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 24 publications
(46 reference statements)
1
46
0
1
Order By: Relevance
“…Many field studies also observed that the changing of window status mostly occurred on arrival of the occupants in office buildings. 12,29 humidity, and CO 2 concentration, described the window opening behavior much better than did the outdoor variables, as shown in Table 3.…”
Section: Discussionsmentioning
confidence: 89%
See 1 more Smart Citation
“…Many field studies also observed that the changing of window status mostly occurred on arrival of the occupants in office buildings. 12,29 humidity, and CO 2 concentration, described the window opening behavior much better than did the outdoor variables, as shown in Table 3.…”
Section: Discussionsmentioning
confidence: 89%
“…The changes in window states mainly occurred in the morning, and the outdoor air temperature significantly influenced the hours of windows opened in the home. Pan et al 12 also showed that the non-environment factors, such as seasonal changes, time of day, personal preference, affect the occupant behavior. For the prediction of the occupant window opening behavior in homes, Yao and Zhao had developed the multivariate linear logistic regression models.…”
Section: Introductionmentioning
confidence: 99%
“…Moghadam et al [60] attempted to simulate the impact of individual behavior on the window state, by implementing Logistic regression models to describe three distinct types of window behavior from active, passive and generalized window users. In 2018, Pan et al [61] analyzed the effects of both environmental and non-environmental factors on window opening/closing behaviors and developed window models using Logistic regression. The study was based on a 9.5-month field measurement for a total of 5 windows in 5 offices on the second floor in Beijing, China.…”
Section: State Of the Artmentioning
confidence: 99%
“…Window opening and closing actions are mainly driven by thermal comfort preferences. In naturally ventilated buildings (as for the case study), ventilation patterns are strictly connected to indoor and outdoor temperature trends [43][44][45]. Light-switching behaviours are related both to visual comfort and habits.…”
Section: Behavioural Modelsmentioning
confidence: 99%